Effectiveness of Sub – Occipital Release Technique for Non-Specific Neck Pain: Life Sciences-Physiotherapy - K, Kirupa; S.M, Divyamary; R, Nithyanisha; G, Vaishnavi; V, Pavithralochini; K, Aarthi; M, Priyanka (International Journal of Life Science and Pharma Research, 2022)
The main objective of the study is to find the effectiveness of sub occipital release technique in neck pain reduction, improving range of movement of neck and improving quality of life. Neck pain has a greater prevalence and is increasing globally because of various causes such as faulty posture, biomechanical causes in cervical, thoracic and scapular region. Tightness in the muscle leads to pain and decreased range of movements. This would reduce the performance of the person in day to day life and slowly will become partially dependent, and this has to be rectified in earlier stage itself. Even though, many research has been performed, they were performed only in the older age group, but not in adult age group. Variability in tension produces impact on structure and functions of cervical muscles. When there is an increased tension in cervical group of muscles, it produces imbalance in tone of the cervical muscles, which leads to neck pain and disturbed daily activities. There are various studies which had proved different methods of treatment involving various modalities, medications, exercises for treating nonspecific neck pain, but the effect of sub-occipital release technique is little understood and practiced. Hence an intervention with low time consuming and evidence based technique is needed. Sub occipital release technique helps to reduce tension in the muscles, thereby helping to perform daily activities effectively. This was an experimental study with pre-post test 20 samples selected from 30 volunteers based on the inclusion criteria. Group A is treated with sub-occipital release technique for 4 weeks, 3 days / week 2 sessions / day (Frequency: 3 times in one session). Control group performs isometric exercise for 4 weeks, 3 days / week 2 sessions / day (Frequency: 3 times in one session). At the end of 30 days of treatment session, there was a significant reduction of neck pain and increased range of motion of neck Flexion from 31.9 to 36.6, Extension from39.2 to45.0, side flexion from13.8 to 18.2, rotation from39.7 to 45.5(mean values), the mean values of VAS and NDI of pretest is 1.4 and 4.94; post test value is1.6 and 2.41.The result concluded that Group A who underwent sub-occipital release technique had more effective treatment in reducing pain and improving range of movements and functional abilities for non-specific neck pain.